Progress in myeloma stem cells - Cruz, Richard Dela (e-Century Publishing Corporation, 2011)
Multiple myeloma (MM) is the second most common hematologic malignancy in the United States and affects about 4 in 100,000 Americans. Even though much progress has been made in MM therapy, MM remains an incurable disease for the vast majority of patients. The existence of MM stem cell is considered one of the major causes of MM drug-resistance, leading to relapse. This highlights the importance and urgency of developing approaches to target MM stem cells. However, very little is known about the molecular characteristics of the MM stem cells, which makes it difficult to target MM stem cells therapeutically. Evidence of the existence of a myeloma stem cell has been provided by Matsui et al. showing that the CD138- and CD20+ fraction, which is a minor population of the MM cells, has a greater clonogenic potential and has the phenotype of a memory B-cell (CD19+, CD27+). In this review, we report recent progress of cell surface markers in cancer stem cells, especially in myeloma and the molecular mechanisms related to drug resistance and myeloma disease progression.